Makings of imagination in alternative cultural spaces in Cairo - Kelada, Mariz (AUC Knowledge Fountain, 2014)
To speak of space as a concept, how it is produced, de/reconstructed, and imagined is a process that involves multiplicities of understanding about the makings that take place. My concern is in this research is exploring the dynamic relationships that take place between cultural spaces in Cairo, the subjectivities of their participants and the possibilities that might be offered through these relations for a different social imagination that could be manifested in the details of their everydayness. The main question of my thesis is; In which ways and conditions can some of the contemporary cultural spaces in Cairo situate their presence and serve as a liberating spaces that nurture imaginations capable of transfiguring the status quo whether intellectual, social or political. My research questions are anchored in four focal theoretical concepts: space, subjectivity, imagination and how these concepts are manifested in everydayness. I will not deal with them as separate, linear or static concepts but as dimensions that are constantly in dynamic change in relation to each other. I will not attempt a cause/effect analysis and I am not after a comparative or a descriptive analysis of the two cultural spaces I chose ( Nahda Association- Jesuit's culture centre in Cairo, The Choir Project of Cairo). I believe this different and dynamic configuration of theorizing will enable different moods of thinking and greater capacity of exploration to acquire different kind of knowledge about the contemporary moment in Cairo's cultural scene, which is rapidly changing and how they can possibly provide fertile conditions for a different social imagination to take place.